The conquistadors and the Aztecs - Sitko, Joseph (Colorado : Chariot [production company] ; Illinois : AGC/United Learning [distributor], 1999)
This program, photographed in Spain and Mexico, takes a look at how Spanish civilization was brought to North America and also a look at the remendous differences that existed between the Aztec and Spanish cultures 500 years ago
Narrator: Lois La Fond
Keywords: Aztecs -- History; Indians of Mexico -- History; Spainish -- History